Pengaruh Partisipasi Siswa Dalam Pembelajaran Dan Proporsi Waktu Belajar Terhadap Hasil Belajar Ips Pada Siswa Kelas VIII SMP Muhammadiyah 05 Kayen Pati Tahun Pelajaran 2016/2017 - Syaikhuddin., Mohammad; , Drs. Sami'an, MM (2016)
The purpose of this study was to determine the effect of student participation in the learning and the proportion of time to learn either partially or simultaneously on learning achievement IPS. This research is quantitative research with associative approach that examine the relationship between variables. The study population was all students of class VIII SMP Muhammadiyah 05 Pati Kayen 2016/2017 school year totaling 124 students. Samples taken as many as 89 students. The sampling technique using proportional sampling. The data collection technique using a questionnaire that had been tested in advance and tested for validity and reliability test. Data analysis technique used is multiple regression analysis, t-test, F, R2 test, as well as the relative contribution and effective. The results showed that: (1) Partisipsi students in learning positive effect on students' learning outcomes IPS at a significance level of 5%. Contributions partisipsi of students in the learning outcomes IPS is equal to 36.1%; (2) The proportion of study time positive effect on the results of social studies students at the significance level of 5%. Contributions proportion of time to learn the results of social studies was 24.5%; (3) Partisipsi proportion of students in learning and learning time together positive effect on learning outcomes IPS eighth grade students of SMP Muhammadiyah 05 Pati Kayen academic year 2016/2017. Overall variable partisipsi influence the proportion of students in learning and learning time contributed 60.6% and the rest influenced by other factors on learning outcomes IPS students. Keywords: Student Participation in Learning, Time Proportion Learning, Learning Achievement IPS